Adolescents' daily sense of school connectedness and academic engagement: Intensive longitudinal mediation study of student differences by remote, hybrid, and in-person learning modality. (February 2023) - McKellar, Sarah E.; Wang, Ming-Te
Abstract: In spring 2020, the COVID-19 pandemic thrust nearly 56 million students in the United States into remote education. By fall 2020, states' and school districts' differing public health measures resulted in the adoption of varying COVID-adapted learning modalities (i.e., in-person, remote, and hybrid). Using daily diary data with a nationally representative sample (N = 517, M age  = 14.65 years), we investigated whether adolescents' academic engagement and connectedness to their teachers and classmates differed by COVID-adapted learning modalities. We also assessed whether adolescent connectedness mediated the link between learning modality and academic engagement. Results revealed that academic engagement and connectedness to teachers and classmates were higher for in-person learners than for students in hybrid and remote learning modalities. Moreover, students' connectedness to classmates and teachers explained the relationship between learning modality and academic engagement. Highlights: COVID-adapted in-person learners had higher academic engagement than other learners. COVID-adapted in-person learners had higher connectedness than other learners. Between- and within-student daily connectedness predicted daily academic engagement. Connectedness fully explained COVID-adapted in-person learners' academic engagement. Connectedness to teachers and classmates mediated paths similarly.